2006
DOI: 10.1073/pnas.0509417103
|View full text |Cite
|
Sign up to set email alerts
|

The Vif and Vpr accessory proteins independently cause HIV-1-induced T cell cytopathicity and cell cycle arrest

Abstract: HIV type I (HIV-1) can cause G2 cell cycle arrest and death of CD4 ؉ T lymphocytes in vitro and inexorable depletion of these cells in vivo. However, the molecular mechanism of viral cytopathicity has not been satisfactorily elucidated. Previously, we showed that HIV-1 kills T cells by a necrotic form of cell death that requires high level expression of an integrated provirus but not the env or nef genes. To determine which viral protein(s) are required for cell death, we systematically mutated, alone and in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
142
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(153 citation statements)
references
References 55 publications
9
142
2
Order By: Relevance
“…More interestingly, several groups recently reported that Vif as well as Vpr induced G2 arrest in HIV-1-infected cells (5,6). Our data clearly demonstrate that the activation of TP53 is the molecular mechanism involved in Vif-induced G2 arrest.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…More interestingly, several groups recently reported that Vif as well as Vpr induced G2 arrest in HIV-1-infected cells (5,6). Our data clearly demonstrate that the activation of TP53 is the molecular mechanism involved in Vif-induced G2 arrest.…”
Section: Discussionsupporting
confidence: 76%
“…It has recently been shown that Vif induces G2 arrest in HIV-1-infected cells independently of Vpr (5,6). To test the possibility that Vif induced G2 arrest by stabilizing and activating TP53, we examined the effect of Vif on cell cycle in various cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, our results show that hnRNP A1 cytoplasmic localization is solely dependent on nucleocytoplasmic transport of the vRNA, via the CRM1-dependent or another pathway. The effects on nuclear import may, however, be a result of a combinatorial effect of viral proteins, as shown for HIV-1-induced apoptosis (76). Although this is not the first study to show hnRNP A1 cytoplasmic localization/retention imposed by a virus, it is the first to report this phenomenon in the context of HIV-1 replication.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, G 2 arrest induced by Vpr may promote virus production by upregulating both transcription (via the LTR) and translation (via the putative HIV-1 IRES) of viral products. Recently, Sakai et al reported that deletion of Vpr, in addition to Vif, rendered HIV-1 incapable of causing G 2 arrest and eliminated the cytopathic properties of the virus, which suggests a link between viral cytopathicity and cell cycle arrest (Sakai et al, 2006). Recently, infected lymphocytes (identified by expression of Gag p24) isolated from recent HIV-1 seroconverters and stained with propidium iodide for DNA content were found to be arrested in G 2 , indicating that G 2 arrest is not merely an in vitro phenomenon (Zimmerman et al, 2006).…”
Section: Vpr-induced G 2 Arrest and Viral Replicationmentioning
confidence: 99%